Modeling the Dynamics of Plunge Milling with Workpiece Vibrations Consideration - Damir, Ahmed (My University, 2010)
Chatter vibrations in machining processes remain one of the major challenges that face the machining process planners to achieve high productivity and product quality. This is mainly due to its undesirable effect that leads to poor surface finish, low part dimensional accuracy, excessive tool wear and reduced productivity. Therefore, for high performance machining, it is extremely important to predict and model the process stability in order to be able to plan the process prior to machining. This will eliminate the need for trials and errors to select the optimum cutting conditions for each operation.
Plunge milling process is becoming an important rough machining operation for die cavities and aerospace parts. This is due to a higher removal rates when compared to other milling processes. This is mainly attributed to the fact that most of the cutting is performed in the axial direction, so that the process can benefit from the spindle rigidity to achieve higher metal removal rates. However, limited published research has been done to model the dynamics and stability of plunge milling and there is a need to study in depth the stability of this process while considering the effect of some parameters not studied in the literature on the process stability.
A time domain simulation model is developed in this research to study the dynamics of plunge milling process for systems with rigid and flexible workpiece. The model predicts the cutting forces, system vibration and process stability by considering the effect of workpiece and tool dynamics, tool setting errors and tool kinematics on chip area evaluation. The dynamic chip area is evaluated based on the interaction of the insert cutting edges (i.e. main and side edges) with the workpiece geometry determined by the pilot hole and surface left by the previous insert. A horizontal approach was used to model the insert geometry to be able to compute correctly the cutting area used in force prediction. This approach considers the contribution of both main and side edge in the cutting zone and is capable of dealing with any geometric shape of the insert. Mechanistic model is used to compute the cutting forces as a function of the dynamic chip area using instantaneous cutting coefficients for each insert to take into account the uneven chip thickness removed by each insert as a result of system vibration and tool setting errors. For the case of a flexible workpiece, the dynamics of the workpiece and milling cutter in three directions, lateral and axial directions, as well as the tool torsional vibration, are considered in the model for accurate prediction of forces and stability limits. The variation of workpiece dynamics according to the hole location is considered in the simulation to model the process stability based on the actual system dynamics as a function of hole location. On the other hand, for a rigid workpiece, only the dynamics of the cutter is considered in the simulation.
Experimental cutting tests with single and double were carried out to check the validity of the simulation model for both cases of plunge milling of rigid and flexible workpiece. Experimental validation for single insert showed the ability of the simulation model to simulate the dynamics of plunge milling with single insert as well as the correctness of the cutting force model.
For case of plunge milling with double inserts, good agreement was found between the measured and the predicted cutting forces and vibration signals and power spectra for case of rigid and flexible workpiece. This indicates the ability of the model to accurately predict cutting forces, system vibration and process stability which makes it very reliable and effective to be used for process planning prior to machining. Both experimental and simulation results showed dominance of workpiece dynamics in the axial direction due to its flexibility as compared to the tool axial rigidity for systems with flexible workpiece. On the other hand, chatter behavior was found to occur due to tool lateral modes for case of rigid workpiece.
Title: Modeling the Dynamics of Plunge Milling with Workpiece Vibrations Consideration, Author: Ahmed Damir, Location: Mills